P.072 Ticagrelor vs Clopidogrel in Addition to Aspirin in Minor Ischemic Stroke/ TIA – a Systematic Review & Network Meta-Analysis (NMA). (November 2021) - Lun, R; Dhaliwal, S; Zitikyte, G; Roy, D; Hutton, B; Shorr, R; Dowlatshahi, D
Abstract : Background: Dual antiplatelet therapy (DAPT) is recommended after minor ischemic stroke/ transient ischemic attack (TIA), but Clopidogrel/ Aspirin has never been compared directly to Ticagrelor/ Aspirin. Our objective is to compare these regimens in terms of efficacy and safety. Methods: Medline, Embase, and Cochrane were searched for randomized controlled trials (RCTs) that enrolled adults with minor stroke/ TIA and administered antiplatelets within 72 hours. The primary efficacy outcome is recurrent stroke or death at 90 days. We performed a Bayesian-approach NMA. Between group comparisons were presented as odds-ratios (OR) with 95% credible intervals (95%CI). Sucraplots were based on calculated probabilities of rankings for individual outcomes. Results: 9/4014 studies were included: 5 RCTs and 4 subgroup analyses. 22, 098 patients were analyzed. At 90 days, both DAPT regimens were superior to Aspirin in the prevention of recurrent stroke/ death. There was no significant difference between Clopidogrel/ ASA compared to Ticagrelor/ ASA (OR 0.90 [95%CI 0.74 – 1.09]), although Clopidogrel/ Aspirin was ranked #1 using Sucraplots. There was no significant difference between the interventions for mortality, bleeding, or adverse events. Conclusions: DAPT was superior to ASA in the prevention of recurrent strokes/ death, but there was no difference between Clopidogrel/ ASA and Ticagrelor/ ASA.